Hospital Costs and Reimbursement Model for a Geriatric Emergency Department. (14th May 2020) - Southerland, Lauren T.; Savage, Elizabeth L.; Muska Duff, Katrina; Caterino, Jeffrey M.; Bergados, Tina R.; Hunold, Katherine M.; Finnegan, Geoffrey I.; Archual, Gregory
Abstract: Objectives: The American College of Emergency Physicians' geriatric emergency department (GED) guidelines recommend additional staff and geriatric equipment, which may not be financially feasible for every ED. Data from an accredited Level 1 GED was used to report equipment costs and to develop a business model for financial sustainability of a GED. Methods: Staff salaries including the cost of fringe benefits were obtained from a Midwestern hospital with an academic ED of 80, 000 annual visits. Reimbursement assumptions included 100% Medicare/Medicaid insurance payor and 8‐hour workdays with 4.5 weeks of leave annually. Equipment costs from hospital invoices were collated. Operational and patient safety metrics were compared before and after the GED. Results: A geriatric nurse practitioner in the ED is financially self‐sustaining at 7.1 consultations, a pharmacist is self‐sustaining at 7.7 medication reconciliation consultations, and physical and occupational therapist evaluations are self‐sustaining at 5.7 and 4.6 consults per workday, respectively. Total annual equipment costs for mobility aids, delirium aids, sensory aids, and personal care items for the GED was 4, 513. Comparing the 2 years before and after, in regard to operational metrics the proportions of patients with lengths of stay > 8 hours and patients placed in observation did not change. In regard to patient safety, the rate of falls decreased from 0.60/1, 000 patient visits to 0.42/1, 000 in the ED observation unit and 0.42/1, 000 to 0.36/1, 000 in the ED. ED recidivism at 7 and 30 days did not change. Estimated cost savings from the reduction in falls was 80, 328. Conclusion: The additional equipment and personnel costs for comprehensive geriatric assessment in the ED are potentially financially justified by revenue generation and improvements in patient safety measures. A geriatric ED was associated with a decrease in patient falls in the ED but did not decrease admissions or ED recidivism.